Peran Teknologi Untuk Membentuk Dinamika Keluarga dalam Novel Sabtu Bersama Bapak Karya Adhitya Mulya - Nazwa Aila Salsabilla; Eva Dwi Kurniawan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The aim of this research is to look at the role of technology in a literary work. The literary work used in this research uses the novel genre entitled Saturday with Father by Adhitiya Mulya. The problem discussed is how technology plays a role in shaping the dynamics of family life in the novel. This includes, among other things, how technology can change the way families communicate, both positively and negatively, and its impact on the dynamics of relationships between family members, then how technology can act as a liaison between family members who are physically separated or otherwise based on the context of the story described. in the novel. The method used in the research uses a hermeneutic approach to explore the role of technology in shaping the dynamics of family life. Through this research, we can understand how technology is not only a tool used in everyday life but also influences how families interact, communicate, and form emotional bonds in their lives.